Pelatihan CorelDraw dalam Perancangan Desain Papan Nama - Linda Santiari, Ni Putu; Rahayuda, I Gede Surya (LPPM Universitas Bumigora, 2023)
Economic growth in Badung Regency is also due to the role of various Small and Medium Enterprises which are currently starting to grow in Badung Regency. One of the trading businesses in Badung district is the UD Memeri (Trade Business) which is located in Banjar Lebah Sari, Gulingan Village, Badung Regency, Bali Province. The constraints faced by the marketing carried out were, the lack of knowledge of trading business owners about graphic design software for making trading business nameplates and the owner's lack of knowledge in making nameplates. There is no trading business nameplate and trading business logo yet. The solution given to this problem is in the form of graphic design software training for making trade nameplate designs and other designs. This training was conducted for the children of UD Memeri owners. The graphic software used is CoralDraw. Training is carried out starting from installing CorelDraw software, making simple designs, assisting in making nameplate designs, exporting design results, and evaluating them. The evaluation process is carried out based on some of the training that has been carried out by giving questions about making a design with the main assessment being the successful completion of the questions. From the results of the evaluation that has been carried out, the results show that the research conducted has a high level of effectiveness ranging from 78% - 86%.